The Interconnection of Certified Cleanliness, Health, Safety and Environmental Sustainability on Purchased Decision Tourism Businesses in Puncak - Hidayat, Candra; Arafah, Willy; Rahmanita, Myrza (Institut Pariwisata dan Bisnis Internasional, 2023)
Cleanliness, health, safety and environmental sustainability or CHSE is the implementation of hygiene, health, safety, and environmental sustainability which is an operational guide for the tourism sector. The purpose of this study is to analyze the interconnection of certified cleanliness, health, safety and environmental sustainability on purchased decision tourism businesses. The sample was 200 respondents from the tourists who experienced at least one time of visiting Puncak. The method used in this research is quantitative method. The questionnaires will be collected by using Google form. The statistical finding there is positive and strong relationship between certified cleanliness, health, safety and environmental sustainability on purchased decision tourism businesses. The finding of this study first, certified cleanliness, health, safety and environmental sustainability very important on purchased decision tourism businesses. Second, the age of respondent between 25 years old until 44 years old with 83 respondents from a total of 200 respondents, this opportunity for tourism businesses to promote a tourism sustainability for young generation. Third, tourism businesses to maintain the price is not higher than other tourist destinations and it is advisable not to increase the prices. Fourthly, according experienced visiting Puncak, more than four-time experience of respondent visiting Puncak with 129 respondents from a total of 200 respondents from all respondents, suggestion for tourism businesses to maintain products, services and innovate by implementing tourism sustainability businesses.